The Appropriate or Optimal Tempo for Music: A Comparison between Non-Musicians and Musicians. (June 2013) - Quinn, Sandra; Watt, Roger
Musicians have enhanced skills that result from intensive training. Whilst musicians show enhanced auditory capabilities (Kraus and Chandrasekaran, 2010 Nature Reviews Neuroscience 11 599–605), non-musicians demonstrate an ability to perform musical tasks (eg listening, dancing, and singing). Non-musicians can also undertake tasks that would normally be reserved for musicians. For example, non-musicians can perceive optimal tempi (ie an appropriate speed) for music (Quinn and Watt, 2006 Perception 35 267–280; Quinn and Watt, 2012 Perception 41 236–238; Quinn et al, 2012 Journal of the Acoustical Society of America 131 3595–3598). This suggests that formalised musical training is not a prerequisite for developing a sense of the tempo that sounds right for a melody. The current studies examine this issue and compare the tempo that musicians choose to perform unfamiliar melodies with the tempo that non-musicians perceive to be optimal for the same melodies. The results demonstrate that the perceived optimal tempo is similar to the performed tempo.